The impact of floods on the economy of the community in North Samarinda District, Samarinda City (Study in Lempake Village, Giri Rejo Village) - Noor, Hamdani; Suharto, Rahcmad Budi; Lestari, Diana (Keynesia : International Journal of Economy and Business, 2025)
This study aims to identify data on the impact of flooding on the economy of the community in North Samarinda District. This study was conducted using a qualitative descriptive method and employed observation, interviews, and documentation. Key informants were taken from the Samarinda City Regional Disaster Management Agency, and residents affected by flooding in Giri Rejo Belimau Village, Lempake Subdistrict, were the data sources. The results of this study show that the impact of flood disasters on the community's economy has caused damage and losses to the irrigation infrastructure sector and economic sectors such as community stalls, cafes, traders, livestock farmers, and farmers. The role of the Regional Disaster Management Agency as the command, coordinator, and implementer in flood disaster management has been carried out well. Various efforts have been made, such as establishing policies, coordinating, and providing facilities for flood disaster management and flood impact mitigation. Although flooding still occurs when rainfall intensity is very high, the government has tried its best to carry out its duties and responsibilities. In addition, the community plays an active role in working together to clean up trash around rice fields, irrigation/ditches, and planting trees to prevent flooding.